Reflection the activation of the sustainability standard NR0401 construction materials to improving product quality - حيدر علي المسعودي; مجيد عبدالله سلام العادلي (Iraqi Journal for Administrative Sciences, 2024)
Sustainability standards are among the most important modern strategies in the field of sustainable development that companies seek to implement to achieve the goal of improving the product by providing sustainable products at low prices that meet the needs, requirements and expectations of customers. The research aims to study the sustainable development standard for industrial laboratories and their application in the Karbala Cement Factory and explain the effect of the NR0401 sustainability standard Construction materials in improving the quality of the customer product in the cement production laboratories, and to identify the possibility of including indicators of the sustainability standard NR0401 construction materials within the tool to publish the quality function QFD because of its Of a role in improving product quality. The research reached a number of conclusions, the most important of which is that technological progress and the intensity of competition between domestic and foreign companies made these companies work to make the customer’s voice their first concern in order to know what he wants from the requirements for the purpose of providing them in the product and in a manner that is reflected in achieving the goal of improving product quality, and that the application of the sustainability standard NR0401 Construction materials positively reflect on improving the product quality. The research sample by meeting the requirements of the customers in good and sustainable products. Therefore, the research recommended preparing the necessary supplies to meet the competition conditions by increasing attention to sustainability issues and standards through As a result of research, studies and improvements on products to achieve their sustainability, this reflects a positive image of the product in the eyes of the customer, enhancing its value.